Changes in Serial D-Dimer Levels Predict the Prognoses of Trousseau's Syndrome Patients - Ito, Shinji; Kikuchi, Koichi; Ueda, Akihiro; Nagao, Ryunosuke; Maeda, Toshiki; Murate, Kenichiro; Shima, Sayuri; Mizutani, Yasuaki; Niimi, Yoshiki; Mutoh, Tatsuro (Frontiers in Neurology, 2018)
Abstract Background: The development of acute multiple embolic infarctions (AMEI) resulting from cancer is known as Trousseau’s syndrome (TS). At present, however, there is no good marker for predicting the prognosis of TS patients. In the present study, we evaluated the use of serial D-dimer levels as a prognostic marker for TS. Methods: This retrospective cohort study included 1,409 consecutive acute ischemic stroke patients. We selected a group of patients with TS showing AMEI (n=38; TS group) and a group of patients with atrial fibrillation (Af) and AMEI (n=35; Af group) as controls. Serial D-dimer levels were measured between days 7 and 28 after stroke (sub-acute phase) in 21 patients of the TS group and 24 patients of the Af group. Results: D-dimer levels at onset (acute phase) were significantly higher in the TS group (8.45 ± 1.79 µg/mL, n=38) compared with the Af group (1.14 ± 0.14 µg/mL, n=35) (p<0.0001). In patients for whom serial D-dimer measurements were made, D-dimer levels measured at the sub-acute phase decreased to 0.48 ± 0.12 µg/mL (n=24) in the Af group, but remained elevated in the TS group during the sub-acute phase (11.20 ± 2.77 µg/mL, n=21) (p<0.0001). In all TS patients in whom serial D-dimer measurements were made, D-dimer levels in 17 patients who died within 500 days (13.31 ± 3.23 µg/mL) were significantly higher than those of the four surviving patients (2.23 ± 0.38 µg/mL) (cut-off D-dimer level = 3.0 µg/mL) during this period. Moreover, serial D-dimer levels of 10 patients who died within 90 days (17.78 ± 4.60 µg/mL) were significantly higher than those of the 11 patients who survived up to 90 days (5.21 ± 2.12 µg/mL) (p<0.05). Conclusions: Serial D-dimer levels may be a good biomarker for TS as well as a useful predictor of the prognosis of TS patients.